Low-Molecular-Weight Heparins (LMWH) and Synthetic Factor X Inhibitors Can Impair the Osseointegration Process of a Titanium Implant in an Interventional Animal Study - Dragos Apostu; Bianca Berechet; Daniel Oltean-Dan; Alexandru Mester; Bobe Petrushev; Catalin Popa; Madalina Luciana Gherman; Adrian Bogdan Tigu; Ciprian Ionut Tomuleasa; Lucian Barbu-Tudoran; Horea Rares Ciprian Benea; Doina Piciu (Medicina, 2022)
Background and objectives: Cementless total hip arthroplasty is a common surgical procedure and perioperative thromboprophylaxis is used to prevent deep vein thrombosis or pulmonary embolism. Osseointegration is important for long-term implant survival, and there is no research on the effect of different thromboprophylaxis agents on the process of osseointegration. Materials and Methods: Seventy rats were allocated as follows: Group I (control group), Group II (enoxaparin), Group III (nadroparin), and Group IV (fondaparinux). Ovariectomy was performed on all subjects, followed by the introduction of an intramedullary titanium implant into the femur. Thromboprophylaxis was administered accordingly to each treatment group for 35 days postoperatively. Results: Group I had statistically significantly lower anti-Xa levels compared to treatment groups. Micro-CT analysis showed that nadroparin had lower values compared to control in bone volume (0.12 vs. 0.21, p = 0.01) and percent bone volume (1.46 vs. 1.93, p = 0.047). The pull-out test showed statistically significant differences between the control group (8.81 N) compared to enoxaparin, nadroparin, and fondaparinux groups (4.53 N, 4 N and 4.07 N, respectively). Nadroparin had a lower histological cortical bone tissue and a higher width of fibrous tissue (27.49 μm and 86.9 μm) at the peri-implant area, compared to control (43.2 μm and 39.2 μm), enoxaparin (39.6 μm and 24 μm), and fondaparinux (36.2 μm and 32.7 μm). Conclusions: Short-term administration of enoxaparin, nadroparin, and fondaparinux can reduce the osseointegration of titanium implants, with nadroparin having the most negative effect. These results show that enoxaparin and fondaparinux are preferred to be administered due to a lesser negative impact on the initial implant fixation.